A Community Empowerment Model through Pesantren-Based Family Empowerment Post (POSDAYA) - Andri Meiriki; Ety Rahayu; Risna Resnawaty (IJEBD (International Journal of Entrepreneurship and Business Development), 2020)
Purpose: This paper aims to analyze A Community Empowerment Model through Pesantren-based Family Empowerment Post (Posdaya). Design/methodology/approach: The method used is composes a reality to be a story, describing a problem, event, phenomenon orderly, followed by analysis and interpretation to analyze the data in a perfect sequence. Findings: 3 hypotheses are rejected while the other 3 is accepted. Research limitations/implications: These components were: 1) Data collection; this was done through interviews. Besides, the data were also collected through a literature study. 2) Data Reduction, after the data were gathered, the researcher focused on removing unnecessary data and arrange the data to gain a conclusion. 3) Data display, this was done through sentences and structured story. 4) Conclusion drawing, this was done to gain full meaning from the processed data, creating a clear, complete synopsis. Practical implications: Results show that from the 3 hypotheses proposed accepted, 1) Pesantren-based Posdaya needs to improve its resources through training or organizational education in order to improve the quality of empowerment program and the continuity of Posdaya activities. 2) Pesantren-based Posdaya needs to strengthen its social capital by establishing stronger social relationships with stakeholders, thus opening accessibility for community empowerment, or family empowerment in particular. 3) Pesantren-based Posdaya should strengthen its organizational structure and workgroup as the program implementer, and continuously monitor the program. Originality/value: This paper is original.